Clinic vs. daily life gait characteristics in patients with spinocerebellar ataxia - Shah, Vrutangkumar V.; Muzyka, Daniel; Jagodinsky, Adam; Casey, Hannah; McNames, James; El-Gohary, Mahmoud; Sowalsky, Kristen; Safarpour, Delaram; Carlson-Kuhta, Patricia; Horak, Fay B.; Gomez, Christopher M. (Frontiers in digital health, 2025)
Recent findings suggest that a single gait assessment in a clinic may not reflect everyday mobility. We compared gait measures that best differentiated individuals with spinocerebellar ataxia (SCA) from age-matched healthy controls (HC) during a supervised gait test in the clinic vs. a week of unsupervised gait during daily life. Twenty-six individuals with SCA types 1, 2, 3, and 6, and 13 (HC) wore three Opal inertial sensors (on both feet and lower back) during a 2-minute walk in the clinic and for seven days in daily life. Seventeen gait measures were analyzed to investigate the group differences using Mann-Whitney -tests and area under the curve (AUC). Ten gait measures were significantly worse in SCA than HC for the clinic test ( < 0.003), but only 3 were worse in daily life ( < 0.003). Only a few gait measures consistently discriminated groups in both environments. Specifically, variability in Swing Time and Double Support Time had AUCs of 0.99 ( < 0.0001) and 0.96 ( < 0.0001) in the clinic, and 0.84 ( < 0.0003) and 0.80 ( < 0.002) in daily life, respectively. Clinical gait measures showed stronger correlations with clinical outcomes (ie, SARA and FARS-ADL; r = 0.50-0.77) than between daily life gait measures (r = 0.31-0.49). Gait activity in daily life was not statistically significant between the SCA and HC groups ( > 0.06). Digital gait measures discriminate SCA in both environments. In-clinic measures are more sensitive, while daily life measures provide ecological validity, highlighting a trade-off and offering complementary insights.